Revision of the subgenus Niphetoscapha Heller of Gymnopholus Heller (Coleoptera, Curculionoidea, Entiminae, Eupholini) and a new species with epizoic symbiosis from West New Guinea - Riedel, Alexander; Kilmaskossu, Agust (Zootaxa, 2017)
The subgenus Niphetoscapha Heller 1914 of Gymnopholus Heller 1901 is revised. It is characterized by the morphology of the elytral apex and the asymmetrical tip of the penis. Vestigial wings and a fused elytral suture indicate flightlessness. Gymnopholus (Niphetoscapha) inexspectatus sp. n. is described as new, exhibiting a distinct epizoic symbiosis with algae otherwise known from the subgenus Symbiopholus Gressitt 1966. The four species of Niphetoscapha inhabit the central mountain range of West New Guinea: Gymnopholus audax Gressitt 1966, G. inexspectatus sp. n., G. nitidus Gressitt & Sedlacek 1967, and G. wichmanni (Heller, 1914). A lectotype is designated for the type-species, G. wichmanni. All species are described, a key is provided, and their distribution is mapped. A large gap separating the areas with records of Niphetoscapha and Symbiopholus is noted for Central New Guinea. The phylogenetic concept of Gymnopholus and its subgenera is briefly discussed.